Two case studies of 129/Sv testicular teratoma - SISKOS, NIKISTRATOS; LELOVAS, PAVLOS; STASINOPOULOU, MARIANNA; KOSTOMITSOPOULOS, NIKOLAOS (Journal of the Hellenic Veterinary Medical Society, 2018)
Testicular teratoma is classified among testicular germ cells tumors. While its incidence is relatively low among animals, in 129/Sv mice is presented in relatively high prevalence. It has been revealed that murine teratoma arises from genetically altered germ cells that undergo malignant transformation during embryogenesis. A point mutation on the 129/Sv genome has been incriminated for failing to regulate normal pathways in germ cell development leading in high teratocarcinogenic risk. For a neoplasm to be characterized as teratoma, derivatives from at least two germ cell layers have to be detected. In the present study, two cases exhibiting all three layers (mesoderm, endoderm, ectoderm) are presented while the tissues observed were of epithelial, connective, muscular, and neural origin. Findings include an almost fully shaped large intestine, a structure closely resembling the heart (blood, endocardium, myocardium) and endochondral ossification.